The Effect of Combined Foot Massage and Leg Elevation on Foot Edema in Third-Trimester Pregnant Women - Meisya Nuraliffa; Yeni Yulistanti; Wiwin Renny Rahmawati; Lulut Handayani (Health and Technology Journal (HTechJ), 2026)
Pregnancy, particularly during the third trimester, is commonly associated with lower-limb edema due to increased pressure on the pelvic veins and inferior vena cava from the enlarging uterus. Foot edema in late pregnancy results from this venous compression, leading to elevated hydrostatic pressure and fluid accumulation in the interstitial spaces of the feet and ankles. Management of foot edema can be performed non-pharmacologically, one approach being a combination of foot massage and leg elevation. The objective of this study was to determine the effect of the combination of foot massage and leg elevation on foot edema in third-trimester pregnant women. This research employed a quasi-experimental study design with a two-group pretest-posttest design and a control group. The sample was 30 respondents. The sampling technique used was purposive sampling. The instruments used were the SOP and the pitting scale observation sheet. Data analysis using the Wilcoxon test showed a p-value < 0.001, indicating a statistically significant reduction in foot edema before and after the intervention. Additionally, the Mann-Whitney test yielded a p-value of 0.003, confirming a statistically significant difference in posttest results between the intervention and control groups. The combination of foot massage and leg elevation significantly reduced foot edema in pregnant women in the third trimester. Clinically, this combination can be applied as a simple and effective non-pharmacological intervention to reduce physiological foot edema during pregnancy.